The influence of gender, parents and background factors on Grade 7 students’ beliefs and attitudes towards mathematics in Mozambique - Murimo, Adelino Evaristo (Faculty of Education, University of the Free State, 2013)
The third study by the Southern and Eastern Africa Consortium for Monitoring Education Quality (SACMEQ) revealed that achievement in mathematics among Grade 6 children in Mozambique is declining, and gender differences favouring boys persist. This study examined the contribution of parents, economic resources and cultural factors on Grade 7 students’ beliefs and attitudes towards mathematics. No gender differences were found, but age, geolocation, number of siblings, education of parent, and possession of economic resources were statistically significant predictors of students’ perceived usefulness of mathematics.
Keywords: Perceived achievement; Perceived usefulness of mathematics; Equity in mathematics learning; Affective domain; Cultural factors